Initial evaluation of the relationship between CYP2C19 polymorphisms and platelet aggregation in patients with acute myocardial infraction in some hospitals in Hanoi - Thi Thuy Mau, Nguyen; Trung, Vu Ngoc; Hieu, Nguyen Huu; Thuy, Nguyen Thanh; Thom, Vu Thi; Long, Dinh Doan; Ha, Trinh Hoang (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 33 No 2, 2017)
CYP2C19 is one of the pricipal enzymes involed in the antiplatelet prodrug in patients with acute myocardial infraction. Different genotypes can cause various responses to platelet aggregation inhibitors. Therefore, we conduct research to evaluate the relationship between CYP2C19 polymorphisms and platelet aggregation in patients with acute myocardial infraction. The study was processed with a cross-sectional study of patients diagnosed acute myocardial infraction had blood samples tested for the gene CYP2C19 and platelet aggregation. The results in 64 consecutive patients, phenotypes based on genotypes: 59,3% poor and intermediate metabolizer, 40,7% extensive metabolizer. The average platelet aggregation of (poor, intermediate) metabolizer and extensive metabolizer were 29,79±13,6 and 23,27±11,6, respectively, there was a high similarity between the groups (p>0,05). The average platelet aggregation of (poor, intermediate) metabolier and extensive metabolizer on the group with Clopidogrel were 26,2±10,5 and 29,9±13,6 (p>0,05), the average with Ticagrelor were 10,8±6,5 and 18,4±8,7 (p>0,05), respectively. The group treated with Ticagrelor had a lower platelet aggregation than the remaining one with Clopidogrel (p<0,01). The study got some initial results that would be important for further studies on the relationship between CYP2C19 polymorphisms and platelet aggregation on Viet Namese patients with acute myocardial infraction.